ULTRASONIC INSPECTION OF LIQUID-FILLED PRESSURE VESSELS USING PIEZOELECTRIC TRANSDUCERS - (:unkn) unknown (My University, 2024)
Automated structural inspection systems employing embedded sensing systems, known as structural health monitoring (SHM), have advanced greatly in recent decades. SHM enables online, real-time damage detection in hard-to-access locations, which can help prevent catastrophic failures. Some of the most advanced capabilities are based on elastic wave propagation in structures, with established capabilities of detecting and locating multiple forms of damage. Advanced capabilities of differentiating forms and extent of damage have recently been established. However, these capabilities are largely limited to simple structures like thin flat plates. Liquid-filled pressure vessels are common in aircraft and spacecraft but pose challenges to elastic wave-based SHM due to a combination of complex geometry and liquid contact that can alter the elastic wave propagation in the structure or transmit elastic waves itself. This work presents an investigation into the ultrasonic SHM of a small liquid-filled pressure vessel to build a physical understanding base of how the ultrasonic wave behaves under changing the states and the pressure under simulated damage. The results show that changing the states of the vessel from empty to full of water will directly affect the second arrivals packet (antisymmetric A0) mode by diminishing the signals and reduction significantly the amplitude of the A0 mode. Moreover, varying the pressure in the pressure vessel also reduces the amplitude of antisymmetric mode A0 for both states empty and full of water.